Capital intelectual (CI) em empresas prestadoras de serviços especializados em contabilidade: um estudo com base na visão dinâmica sobre CI - Werninghaus, Hugo Ludwig (2024)
This study analyzes Intellectual Capital in accounting service firms in Brazil, focusing on the creation, management, and protection of this capital, which is essential for organizational performance. The aim was to investigate the interactions between observed and latent components of intellectual capital by applying exploratory factor analysis (EFA) and structural equation modeling (SEM) using the statistical software RStudio. This methodological approach allowed an in-depth investigation of the structure and dynamics of Intellectual Capital, providing a basis for strategies to optimize it. The research encompasses Human, Structural, Relational, and Renewal Capital, drawing on the research and models of Kianto et al. (2010 and 2018). The results were obtained through a survey conducted with HR and personnel management professionals in accounting and auditing firms in São Paulo, with a sample of 71 valid respondents. The results highlight a positive correlation between Human and Renewal Capital for the creation of Intellectual Capital in accounting organizations. The study contributes by enhancing the understanding of effective Intellectual Capital management, the importance of competitive advantage, and organizational performance, suggesting that managers of accounting firms should adopt strategies that prioritize both the development and protection of intellectual capital. Despite demonstrating geographic and sample limitations, it recommends future research. In summary, this study reinforces the strategic relevance of intellectual capital in Brazilian accounting firms and proposes continuous improvements in management practices